2008
DOI: 10.1118/1.2897966
|View full text |Cite
|
Sign up to set email alerts
|

The DosiMap, a new 2D scintillating dosimeter for IMRT quality assurance: Characterization of two Čerenkov discrimination methods

Abstract: New radiation therapy techniques such as IMRT present significant efficiency due to their highly conformal dose distributions. A consequence of the complexity of their dose distributions (high gradients, small irradiation fields, low dose distribution, ...) is the requirement for better precision quality assurance than in classical radiotherapy in order to compare the conformation of the delivered dose with the planned dose distribution and to guarantee the quality of the treatment. Currently this control is m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 34 publications
2
39
0
Order By: Relevance
“…In a sense, this portion of the Čerenkov light becomes a source of contamination, analogous to the stem effect in plastic scintillation dosimetry and could be reduced by using an optical filter centered on the fluorescent emission peak, or fully removed using spectral or temporal methods (Frelin et al , 2008; Liu et al , 2011; Therriault-Proulx et al , 2011). All three potential sources of error will be investigated in a future study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a sense, this portion of the Čerenkov light becomes a source of contamination, analogous to the stem effect in plastic scintillation dosimetry and could be reduced by using an optical filter centered on the fluorescent emission peak, or fully removed using spectral or temporal methods (Frelin et al , 2008; Liu et al , 2011; Therriault-Proulx et al , 2011). All three potential sources of error will be investigated in a future study.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of profiling static megavoltage linear accelerator (LINAC) beams for routine quality assurance (QA), typically only a small subset of the full volumetric dose is directly measured by virtue of an ionization chamber measurement in water. Several methods have been proposed to move towards 2D and/or full 3D beam profiling without the use of ionization chambers, including techniques that use plastic or liquid scintillators, as well as gel-based dosimetry (Beddar et al , 1992a; Beddar et al , 1992b; Frelin et al , 2008; Collomb-Patton et al , 2009; Guillot et al , 2011; Kirov et al , 2000; Ponisch et al , 2009; Beddar et al , 2009; Archambault et al , 2012; Maryanski et al , 1994; Maryanski et al , 1996; Kelly et al , 1998; McJury et al , 2000). However, both methods have limitations in that they are not truly water equivalent.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have demonstrated that plastic scintillators are excellent detectors for use in clinical radiation dosimetry . Several factors contribute to their suitability.…”
Section: Introductionmentioning
confidence: 99%
“…However both detector designs are limited to a single 2D imaging plane perpendicular to the direction of the beam and thus no depth dose distribution can be directly measured. Recently, Frelin et al 7 presented a new 2D scintillation dosimeter for IMRT QA, which consisted of a plastic scintillating sheet placed inside a transparent polystyrene phantom, and investigated methods to correct for Čerenkov radiation. Kirov et al 8 investigated the use of liquid scintillators for brachytherapy applications and, therefore, studied the dosimetric properties of different scintillating solutions with the aim of developing water equivalent dosimeter media at the lower energies that are suitable for use with the most commonly used radioactive sources.…”
Section: Introductionmentioning
confidence: 99%